HEPATITIS - Asranov Sardor Azimjonovich (PEDAGOGS, 2024)
Annotation: Hepatitis, an inflammation of the liver, affects millions globally and presents significant public health challenges. This article explores the various types of hepatitis, their causes, symptoms, and global impact. It also reviews the existing literature, analyzes methods of diagnosis and treatment, and discusses strategies for prevention and management.